Development and Validation of Activity Based Learning Scale among Teachers - Ritu Samaddar; Deb Prasad Sikdar (Iranian Journal of Educational Research)
Objective: Activity Based Learning (ABL) is a method where students continuously engage in tasks and think about them, helping them understand the teacher's desired outcomes. Classroom management is crucial for creating a conducive learning environment, allowing teachers to control the learning style and direction, preventing disruptions and discomfort. The study aimed to develop an Activity-based learning (ABL) tool related classroom management for teachers in West Bengal, India. It also aimed to determine their views on classroom management scale. Methods: The study used convenience sampling from larger populations to estimate the number of teachers in various cities. The study involved 100 teachers who were given a self-administered version of a 28-item Activity-based learning (ABL) scale. Results: After item analysis, the scale had 25 items remaining, covering six broad dimensions: Time Management, Content Complete, Student Interest, Class Control, Child Psychology, Preparation. Secondly The data analysis process included 306 teachers' responses in a second data set for Cronbach alpha. A high degree of statistically significant correlation was found in the scale's final iteration, with Cronbach alpha values of 0.724. Conclusions: The comprehensive analysis revealed that the Activity-Based Learning (ABL) instrument serves as an effective tool for evaluating classroom management among teachers in the West Bengal region of India.